Enhancer-dependent gene regulation in space, time, and malignancies - Blum, Belinda; Dachtler, Victoria; Feldmann, Angelika (International journal of cancer, 2025)
Control of cell-type-specific gene activation requires the coordinated activity of distal regulatory elements, including enhancers, whose inputs must be temporally integrated. Dysregulation of this regulatory capacity, such as aberrant usage of enhancers, can result in malignant transformation of cells. In this review, we provide an overview of our current understanding of enhancer-driven gene regulation and discuss how this activity may be integrated across time, followed by epigenetic and structural alterations of enhancers in cancers.
Online veröffentlicht: 31 January 2025
Gesehen am 26.08.2025